lo g x 1 / x a = 1 + lo g x lo g m a a
In the above equation, the first logarithm has base x 1 / x , and the second logarithm has base x raised to the power of lo g m a .
Let m , a be real numbers where m > 0 , a > 1 , such that the equation above has exactly one real solution for x ; suppose that this solution is x = n . Let
P = 3 n 2 ( m + n ) ( m n + n 2 ) 3 − m 3 n 3 − n 6
Compute the value of ⌊ 1 0 3 ⋅ a P ⌋ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
The identity lo g p q = lo g q p 1 applies to the given eqation . lo g x 1 / x ( a ) = 1 + lo g x lo g m a ( a ) ⇒ lo g a ( x 1 / x ) 1 = 1 + lo g a ( x lo g m ( a ) ) 1 ⇒ x 1 lo g a ( x ) 1 = 1 + lo g m ( a ) lo g a ( x ) 1 ⇒ x = lo g a ( x ) + lo g a ( m ) ⇒ x = lo g a ( m x ) ⇒ a x = m x This can be interpreted as the intersection between curve y = a x and line y = m x . Given m > 0 and a > 1 so, one solution is only possible when line y = m x is tangent to the curve y = a x at x = n . For y = a x , d x d y = a x ln a At x = n , a n = m n . . . . . . . . . ( 1 ) and ( d x d y ) x = n = m = a n ln a . . . . . . . . . ( 2 ) ( 1 ) and (2) ⇒ m n ln a = m ⇒ ln a = n 1 ⇒ a = e n 1 and m = ( e n 1 ) n ln ( e n 1 ) ⇒ m = n e Now, substituting these results for m and a into the given expression, ⌊ 1 0 3 a 3 n 2 ( m + n ) ( m n + n 2 ) 3 − m 3 n 3 − n 6 ⌋ = ⌊ 1 0 3 a 3 n 2 ( m + n ) m 3 n 3 + n 6 + 3 n 4 m ( m + n ) − m 3 n 3 − n 6 ⌋ = ⌊ 1 0 3 a n 2 m ⌋ = ⌊ 1 0 3 ( e n 1 ) n 2 × n e ⌋ = ⌊ 1 0 0 0 e e ⌋ = 1 5 1 5 4